An infant with hypertriglyceridemia presenting as failure to thrive: a case report - Srinivas, Rajesh K.; Gupta, Ashok; Mathur, Priyanshu; Agarwal, Kamlesh; Sharma, Anil (International Journal of Contemporary Pediatrics, 2021)
Familial hypertriglyceridemia is rare in infancy. Diagnosis in infancy is very difficult and is usually diagnosed when acute pancreatitis sets in. Early diagnosis is important as it can prevent the complications associated with acute pancreatitis and pancreatic necrosis. Here is a case familial hypertriglyceridemia in an infant who presented to us with failure to thrive but was diagnosed early due to presence of highly viscous and milky blood. This holds importance as early treatment can reduce the complications and morbidity associated with familial hypertriglyceridemia.